Integrating Social-Emotional Learning to Improve Academic - Valerie Zelenka (The Advocate, 2016)
The benefits of integrating social-emotional and academic instruction have been well documented. Students excel academically and experience fewer behavioral challenges when teachers accommodate social-emotional and academic needs simultaneously. This paper outlines some of the specifics of doing this.